Struktur, Fungsi, dan Makna Mantra Pengasih Diri di Desa Sungai Nyirih, Kecamatan Selakau serta Implementasinya di Sekolah - Zulfahita Zulfahita (Jurnal Pendidikan Bahasa, 2020)
This study aims to describe the structure, function, and meaning of self-compassion mantra in Nyirih river Village, Selakau District. The research method used a descriptive method with a qualitative form, using a structural approach. Data collection tools using observation sheets, interviews. The technique of analyzing data in this research is transcription, data classification, analysis, and inference. Based on the results of data analysis carried out on 15 self-compassion mantras, the following results were obtained. In the 15 spells studied, there are spell structures, namely the elements of title, opening, intention, suggestion, purpose, and closing, with the function of the mantra, 1 quote serves as a conqueror of evil, 13 quotes serve as filler of supernatural powers, 15 quotes serve as a medium of communication with God, 7 quotes serve as a charm for romance, and 2 quotes serve as shackles for the human spirit and the jinn. While the meaning of the mantra contained in the 15 mantras has a connotative meaning. This research was implemented in the seventh grade junior high school odd semester, with KD 3.14 and 4.14 material of folk poetry.